SUPERIORITY OF THE POLICY TO ATTRACT FOREIGN DIRECT INVESTMENT (FDI) CAPITAL OF VIET NAM THROUGH THE US - CHINA TRADE WAR - Mai Xuan Dao, Nguyen Thi Cam Loan, Nguyen Hoang Phuong, Vu Van Vien, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Basic contents of the Politburo's Resolution No. 35-NQ / TW on firmly defending the Party's ideological foundation, and fighting against wrong and hostile views in the new situation; at the same time, strengthening the work of grasping public opinion to contribute to maintaining solidarity and unity in the Party, social consensus and people's beliefs with the Party; prevent and reverse the decline in political ideology, morality, lifestyle, the manifestations of "self-evolution", "self-transformation" internally; to defeat all intrigues, tricks and anti-sabotage activities of hostile forces, reactionaries in the new situation. From that important point, the author wanted to write a paper entitled "The superiority of the policy to attract FDI in Vietnam is expressed through the US-China trade war" to affirm that the policy of the Party and The State of Vietnam is right, refutes any untrue information, distorts the Party's viewpoint, in order to contribute to repelling bad people against our country.